A Systematic Literature Review: Development of Physics Learning Research with Project-Based Learning Model in Indonesia - Suwasono, Purbo; Salmah*, Ummi; Mercado, Justine C; Kurniawan, Robi (Universitas Syiah Kuala, 2024)
Project based learning (PjBL) plays a crucial role in helping students develop 21st-century skills. This study aims to assess the development of PjBL implementation in physics education in Indonesia through a systematic literature review. By analyzing articles published between 2017 and 2023, this research employs identification, screening, and in-depth analysis techniques to evaluate the content. Inclusion and quality assessments of the articles are conducted meticulously to ensure accuracy and avoid bias. A total of 24 relevant articles were identified, with most studies being experimental and involving high school students with sample sizes ranging from 22 to 48 students. The most common research instrument was tests, focusing on fluid topics, and the frequently measured variable was students' creative thinking skills. PjBL is often integrated with the STEM approach. Recommendations from this review include the development of PjBL on a wider range of physics topics and more comprehensive measurement of students' skills. Teachers are also advised to manage time allocation effectively when implementing PjBL. The limitation of this study is its exclusive focus on PjBL in Indonesia. Further research is recommended to explore the application of PjBL in enhancing critical thinking, problem-solving, and student literacy in less commonly tested physics topics such as Newton's Laws, Temperature and Heat, Electromagnetism, Light, and Waves